2007
DOI: 10.1080/01421590701724741
|View full text |Cite
|
Sign up to set email alerts
|

Medical education in the Netherlands

Abstract: This paper aims to draw a picture of current medical education in The Netherlands. Based on strong historical roots in the seventeenth century, Dutch medical education has adapted to changing circumstances through the ages. Nowadays, medical education in The Netherlands may be called "modern", according to international standards and schools such as the one in Maastricht serve as examples, nationally and internationally. After considerable redesign of undergraduate education in the 1980s and 1990s, the first d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
98
0
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 137 publications
(102 citation statements)
references
References 12 publications
1
98
0
3
Order By: Relevance
“…In the Netherlands students for medical school are in part admitted by lottery and in part selected by a medical school-specific selection procedure (Ten Cate 2007). This situation presents a unique control group of randomly (lottery-) admitted students compared with those selected by a school-specific procedure which at our medical school combined nonacademic (puECAs) and academic (cognitive tests) criteria (Urlings-Strop et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In the Netherlands students for medical school are in part admitted by lottery and in part selected by a medical school-specific selection procedure (Ten Cate 2007). This situation presents a unique control group of randomly (lottery-) admitted students compared with those selected by a school-specific procedure which at our medical school combined nonacademic (puECAs) and academic (cognitive tests) criteria (Urlings-Strop et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The literature on selection mainly contains single-site studies and studies investigating selection tools in isolation, rather than combinations of selection tools (Patterson et al 2016). This multi-site study aims to fill these gaps by examining the value of (different) selection procedures compared to a weighted lottery procedure, which is weighted for pre-university grade point average (pu-GPA) and includes direct admission for students with top-pu-GPAs (C8 out of 10) (Ten Cate 2007). Outcomes of interest were student performances, as well as motivation (for studying medicine) and engagement in learning, because these variables are deemed important for the learning, performance and well-being of students (Casuso-Holgado et al 2013;Prins et al 2009;Williams et al 1999).…”
Section: Introductionmentioning
confidence: 99%
“…In one study it was shown that medical students had a negative attitude towards basic sciences, including anatomy and they believed that there was no association between theoretical and practical aspects of these sciences and they could not use the theoretical sciences in clinical situations (9). Another study on interns showed that they did not have a positive attitude towards use of basic sciences in wards and on patients' bedsides (10,11). Some studies have stated that the negative attitude towards basic sciences, especially anatomy, is due to the lack of consistency between theoretical and clinical aspects (12,13).…”
Section: Introductionmentioning
confidence: 99%